Kyle Daniels: capstone - Daniels, Kyle, artist (Colorado State University. Libraries, 2017)
The artist's statement: Within design work the use of imagery is largely to portray a visual message for the viewer to grab and hold their attention. Doing so in creative ways requires thinking outside the realm of only digital design. As a graphic designer, it is important to me to bring in elements from traditional arts as well. Incorporation of techniques such as watercolor can create textures and effects that are difficult to authentically replicate digitally. Using multimedia in graphic design can allow for different effects on the viewer as well. Using some elements of traditional media allows for more creative freedom when designing can sometimes feel stifling, and allows for more self investment. Within my works I blend forms of traditional media, and have a more illustrative digital style. I often times start with traditional media in sketches or watercolor and ink before moving onto incorporating it in digital form. My work is usually serious or focuses on a dry humor and utilizes strong contrasts of lines and color. I prefer to focus more on the illustration and allowing the image to speak for itself rather than words when allowed.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design